Broadband dielectric and conductivity spectroscopy of inhomogeneous and composite conductors. Issue 11 (29th August 2013) - Petzelt, Jan; Nuzhnyy, Dmitry; Bovtun, Viktor; Savinov, Maxim; Kempa, Martin; Rychetsky, Ivan
Abstract Present facilities in the Department of Dielectrics, Institute of Physics ASCR, enable us to study the complex dielectric/conductivity response of various dielectric, semiconducting and poor‐metallic conducting materials and their composites in the frequency range of 10−5–1014 Hz (19 orders of magnitude). Here we summarize the phenomenological models used for fitting and basic understanding of such spectra, particularly of weak inhomogeneous and disordered conductors and composite conductor–dielectric materials within the effective medium approach. For the latter type of materials the electrical percolation phenomena are discussed. The obtained experimental results on several conductor–dielectric composites, particularly around their percolation threshold (PET‐CNT, alumina‐CNF, PZT‐PRO), porous conducting pellets (MoSI, WS2), nanofiber matrix (PVDF‐WS2), and variously conducting polyaniline pellets are briefly discussed.